PENGARUH PENGGUNAAN ALAT PERAGA TERHADAP HASIL BELAJAR MATERI BENTUK ALJABAR PADA SISWA SMP NEGERI 1 NDONA - Theresia Yunita Mudamakin; Maria Fatima Mei; Yasinta Yenita Dhiki (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
The aim of this research is to determine the effect of using teaching aids in improving student learning outcomes in algebra material. This research uses quantitative research methods. This research was carried out at SMP Negeri 1 Ndona, with the population taken being all class VII students of SMP Negeri 1 Ndona totaling 175 people with a class size of 5. The sampling technique used in this research was probability sampling (random). Therefore, class IV A students were selected as the experimental class and class IV B students were selected as the control class. The instrument used is a test, with data analysis techniques using the SPSS for Windows program. Based on the tests that have been carried out, there is a significant influence in the use of teaching aids on student learning outcomes in algebra form at SMP Negeri 1 Ndona. This can be seen from the results of the hypothesis test tcount> ttable or 8.871> 1.668 and sig. < 0.05 or 0.00 > 0.05 then Ho is rejected. So it can be concluded that there is an influence of the use of teaching aids on learning outcomes.